A Survey of Pharmacogenomics Testing Among Physicians, Pharmacists, and Researchers From China - Guo, Chengxian; Hu, Biwen; Guo, Chengjun; Meng, Xiangguang; Kuang, Yun; Huang, Longjian; Wang, Danling; Xu, Kangwei; Zhao, Yanlin; Yang, Guoping; Cai, Weimin; Shu, Yan (Frontiers in Pharmacology, 2021)
To elucidate current domestic factors influencing pharmacogenomics (PGx) implementation and its future in China, we conducted a questionnaire survey on PGx applications and testing. A questionnaire-based survey was created on the popular online professional survey platform 'Wenjuanxing' (www.wjx.cn) and performed via the social media platform WeChat. Among 422 participants, there were physicians (27.7 %), pharmacists (31.3 %), and researchers (41.0%). We found that less than 50% of physicians were aware of the importance of PGx in drug therapy, while over 50% of pharmacists and researchers recognized the importance. Only 38.5% of physicians, 40.9% of pharmacists, and 55.5% of researchers concurred that PGx analysis could lower the economic burdens for patients. However, most of the responders affirmed that PGx should be effectively implemented in clinical practices. A lack of sector standards, a lack of clinical research, and a lack of guidelines were found to be the major factors for hindering PGx clinical application. Among drugs associated with PGx assays, the most common were warfarin and clopidogrel. Although PGx research has advanced rapidly in recent years in mainland China, the clinical implementation of PGx has a long way to go.